Pharmacogenetics and interactions of antidepressants in the treatment of co-morbid illness - Mihaljević-Peleš, Alma (Array, 2009)
Patients who require long-term treatment for depression have an increased risk of experiencing drug interactions since they will take medications for and/or co-morbid illness. Antidepressants can be the object of drug interactions by other substances, or they can precipitate interactions by inhibiting enzyme pathways. Specific antidepressants differ in the interactions with CYP450 isoenzymes and in their susceptibility to drug-drug interactions. The main focus of this article is pharmacokinetic drug interactions of antidepressants. With that specific knowledge, clinicians can improve outcomes of depressed patients, by considering the possibility of drug interactions both before prescribing a specific antidepressant and while monitoring for response, adverse effects and patient compliance